Circular economy in the olive oil value chain: assessment of by-product generation in the main olive-growing area of Argentina, San Juan - Renzi, L. (2025)
Fil: Renzi, L. Instituto Nacional de Tecnología Industrial. Sede San Juan (INTI-San Juan); Argentina